2021
DOI: 10.1177/0363546521994558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Osteochondral Autograft Transplantation and Arthroscopic Fragment Resection for Large Capitellar Osteochondritis Dissecans in Adolescent Athletes: A Minimum 5 Years’ Follow-up

Abstract: Background: The choice of surgical option for unstable large capitellar osteochondritis dissecans (OCD) lesions in skeletally immature athletes remains controversial. Purpose/Hypothesis: The purpose was to investigate functional and radiographic outcomes after arthroscopic fragment resection and osteochondral autograft transplantation (OAT) for unstable large capitellar OCD lesions in skeletally immature athletes with a minimum 5 years’ follow-up. We hypothesized that the outcomes after OAT for large capitella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The amount of bone on the posterior aspect of the cartilage fragment may be predictive as to whether the fragment can be arthroscopically repaired. Based on arthroscopic evaluation, excision of an unstable/nonviable osteochondral fragment of the capitellum with microfracture vs. arthroscopic fixation of viable fragments may be performed 13,14 (Figs. 11 through Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of bone on the posterior aspect of the cartilage fragment may be predictive as to whether the fragment can be arthroscopically repaired. Based on arthroscopic evaluation, excision of an unstable/nonviable osteochondral fragment of the capitellum with microfracture vs. arthroscopic fixation of viable fragments may be performed 13,14 (Figs. 11 through Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical treatment is principally recommended to the patients who have persistent pain, locking phenomenon, severe restriction of elbow motion, fragment displacement, wide gap between the progeny fragment and the parent bone, irregular contour or defect of the articular surface, and T2 high signal interface through the articular cartilage. 46 , 71 , 84 Surgical procedures include arthroscopic removal of the lesion with or without drilling and microfracture, 5 , 8 , 34 , 50 , 97 fragment fixation, 18 , 22 , 44 , 65 , 64 , 95 , 101 autologous chondrocyte implantation, 27 osteochondral autograft transplantation (OAT), 1 , 15 , 25 , 42 , 45 , 48 , 62 , 72 , 73 , 74 , 76 , 77 , 78 , 96 wedge osteotomy, 33 osteochondral allograft, and various novel techniques. 47 , 59 , 60 Candidate donor sites for OAT include the non-weight-bearing area of the lateral femoral condyle and the transitional area between the rib and its associated cartilage.…”
Section: Treatmentmentioning
confidence: 99%
“… 47 , 59 , 60 Candidate donor sites for OAT include the non-weight-bearing area of the lateral femoral condyle and the transitional area between the rib and its associated cartilage. 1 , 15 , 25 , 42 , 45 , 48 , 60 , 73 , 74 , 76 , 77 , 78 , 96 , 101 …”
Section: Treatmentmentioning
confidence: 99%
“…14 While the age of the patient, size and stability of the lesion, level of overhead activity, and surgeon preference help delineate surgical treatment, stud ies directly contrasting treatment arms have found similar results among operative cohorts. 15,16 While the specific cause of elbow osteochondral lesions may be multifactorial, there is increasing interest in identi fying risk factors for its development. The purpose of this study was to investigate the association between patients requiring surgery for elbow osteochondral lesions and prior supracondylar humerus or lateral condylar pinning, including evaluating patient demographics, imaging find ings, and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 14 While the age of the patient, size and stability of the lesion, level of overhead activity, and surgeon preference help delineate surgical treatment, studies directly contrasting treatment arms have found similar results among operative cohorts. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%